Kajian Strategi Pengendalian Pencemaran Sub Daerah Aliran Sungai (DAS) Kali Dendeng Kota Kupang - Philiphi de Rozari (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2017)
Kali Dendeng is important river for Kupang citizen because the water resources from Kali Dendeng are used by the communities for domestic, agriculture, animal husbandry and small industries purposes. This research aims to; (1) to determine the physical and chemical condition of the waters of Kali Dendeng and to analyze the water quality of Kali Dendeng River and to determine the load of the pollutant based on several water quality parameters; (2) to identify sources and types of pollutants in wastewater and river water; (3) to identify the role of various stakeholders in Kali Dendeng to achieve sustainable use of water resources and to protect the environment. The study was conducted by measuring several water quality parameters such as turbidity, conductivity, pH, DO, COD, BOD, TSS, N-Nitrite, P-PO43-, oils and fats, detergents and coliform bacteria in several sampling points and distributing questionnaires to decision makers and communities living in Kali Dendeng River Basin. The results showed that BOD, oil and fat, and coliform concentrations in Kali Dendeng had exceeded the threshold specified in accordance with Government Regulation No.82 of 2001. In addition, water quality status using STORET INDEX analysis showed that sub DAS Kali Dendeng was categorized medium contaminated with BOD load = 29,448 kg / day and COD load = 56, 540 kg / day. The waste disposal from septic or greywater, disposal of tofu industry waste, and pig farm waste was the major contribution of water pollution in Kali Dendeng.